Deciphering the molecular basis for photosynthetic parameters in Bambara groundnut (Vigna subterranea L. Verdc) under drought stress - Xiuqing Gao; Hui Hui Chai; Wai Kuan Ho; Sean Mayes; Festo Massawe (BMC Plant Biology, 2023)
Abstract Background Assessment of segregating populations for their ability to withstand drought stress conditions is one of the best approaches to develop breeding lines and drought tolerant varieties. Bambara groundnut (Vigna subterranea L. Verdc.) is a leguminous crop, capable of growing in low-input agricultural systems in semi-arid areas. An F4 bi-parental segregating population obtained from S19-3 × DodR was developed to evaluate the effect of drought stress on photosynthetic parameters and identify QTLs associated with these traits under drought-stressed and well-watered conditions in a rainout shelter. Results Stomatal conductance (gs), photosynthesis rate (A), transpiration rate (E) and intracellular CO2 (Ci) were significantly reduced (p < 0.05) while water use efficiency (WUE) was significantly increased (p < 0.05) under drought-stressed conditions. A strong linear correlation was observed between gs, WUE, A, E and Ci under both water regimes. The variability between different water treatment, among individual lines and the interaction between lines and environment for photosynthetic parameters provides resources for superior lines selection and drought resistant variety improvement. Significant QTL for gs and F V /F M under well-watered conditions were mapped on LG5 and LG3, respectively, with more than 20% of the PVE, which could be considered as the major QTL to control these traits. Five clustered QTLs for photosynthetic traits under drought-stressed and well-watered conditions were mapped on LG5, LG6A, LG10 and LG11, respectively. Conclusions Significant and putative QTLs associated with photosynthetic parameters and the effect of drought stress on these traits have been revealed by QTL linkage mapping and field experiment in the F4 segregating population derived from S19-3 × DodR in bambara groundnut. The study provides fundamental knowledge of how photosynthetic traits response to drought stress and how genetic features control these traits under drought-stressed and well-watered conditions in bambara groundnut.